Malaysian teachers’ perceptions on using the listening materials from get smart plus 4 English textbook - Mohan, Madhawhan Nair (2021)
The present study evaluated the listening materials of Get Smart Plus 4, an official textbook used for Primary 4 pupils in all primary schools nationwide in Malaysia. In previous studies, textbook evaluation was quite popular with researchers in an overall or general way where all the basic language skills were included. Some researchers often assessed the reading and writing parts of coursebooks. Unfortunately, there was a lack of studies on the evaluation of listening skills due to not being exam-orientated. In addition, previous studies were likely to use only interviews as a research instrument to know the teachers' opinions using the textbooks. However, in this research, a case study research design was conducted utilising the descriptive qualitative method, which includes interviews and document analysis. Data were collected from 7 English primary school teachers around the Kulai district currently teaching Primary 4 or had previously taught using the Get Smart Plus 4 English textbook. Document analysis was also carried out on the Get Smart Plus 4 English textbook using a textbook evaluation checklist. The evaluation was important to find out the perception of the teachers on using the listening materials of the Get Smart Plus 4 English textbook as well as the effectiveness of the Get Smart Plus 4 English Textbook in enhancing the students’ listening skills. Based on the textbook evaluation results, most experts agree that the Get Smart Plus 4 English textbook is suitable for the Primary four teachers in teaching the listening activities in class. Furthermore, the researcher found an adequate amount of listening materials and activities to assist the pupils in acquiring the listening skill. However, the textbooks need to be improved by making a specific listening module to help teachers concentrate on the listening skill and add more authentic listening materials connected with the Malaysian context.